A comic page for the first isomorphism theorem. Issue 1 (3rd April 2022) - Cosme Llópez, Enric; Ruiz Mora, Raúl; Tamarit, Núria
Abstract : Given a homomorphism between algebras, there exists an isomorphism between the quotient of the domain by its kernel and the subalgebra in the codomain given by its image. This theorem, commonly known as the first isomorphism theorem, is a fundamental algebraic result. Different problems have been identified in its instruction, mainly related to the abstraction inherent to its content and to the lack of conceptual models to improve its understanding. In response to this situation, in this paper, we present an illustration that explores the narrative and graphical resources of comics with the aim of describing the set-theoretic elements that are involved in the proof of this theorem. GRAPHICAL ABSTRACT: UF0001